Vers une tentative d’uniformisation du traitement accentuel des composés savants suffixés en anglais contemporain - Pierre Fournier (Anglophonia)
The stress assignment of suffixed neoclassical compounds in contemporary English is complex. Taking the morphological boundaries and the influence of bases into account seems to highlight the importance of these bases on the primary stress location. According to this attractiveness-based parameter, bases are labelled as attractive, non-attractive or half-attractive. This article questions the validity of this classification, whose conclusions were first drawn with -ous, by analysing the stress patterns of neoclassical compounds which are suffixed in -al. The choice of -al is determined by the similar properties these two suffixes both share. The creation of a typology of bases, which could be built according to the attractiveness-based concept and could be effective no matter what the suffix may be, turns out to be problematic as other factors appear to be fundamental regarding to stress location.